If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4M + -9 = -3 + 6M Reorder the terms: -9 + 4M = -3 + 6M Solving -9 + 4M = -3 + 6M Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-6M' to each side of the equation. -9 + 4M + -6M = -3 + 6M + -6M Combine like terms: 4M + -6M = -2M -9 + -2M = -3 + 6M + -6M Combine like terms: 6M + -6M = 0 -9 + -2M = -3 + 0 -9 + -2M = -3 Add '9' to each side of the equation. -9 + 9 + -2M = -3 + 9 Combine like terms: -9 + 9 = 0 0 + -2M = -3 + 9 -2M = -3 + 9 Combine like terms: -3 + 9 = 6 -2M = 6 Divide each side by '-2'. M = -3 Simplifying M = -3
| 4x-11=6x+10 | | 0=16t^2+64t+8 | | 7(c+4)whenc=8 | | 2-3x-4=10 | | 8x+5=2(3x+1) | | 6a-2whena=7 | | -x+3=3x^2-8x+5 | | 0=12-P^2-Q | | f=9/5(-12)+32 | | 10-29u+10u^2=0 | | 4y-4(5y-5)=2-4(-2-y) | | 9x-3-2=6.8+8x | | f=9/5(43)+32 | | Q=12-P^2 | | -3(t-2)+20=2(t+3) | | 14b+31=15-2b | | 7ax^2+21x^2= | | 2(-m+10s)= | | 2x+10y+10=0 | | 49b^2+f^2-14bf=0 | | 16(f+9)=10f+204 | | 8(x-3)-4=2x+8 | | 27=100x-2x^2 | | 5x-3=3+8x | | 112=-x+193 | | 3m-8=-3+5m | | -4-3a=-3a-4(a+2) | | 1=1+5x+2x | | X^2+3x+51=0 | | -[6x-(2x+6)]=-1-[6(2x-5)-6x] | | 2a-2=-3a+23 | | 3w-6x-y+5w+17x-6y= |